A heuristic algorithm to schedule twin yard crane to Mmnimize job tardiness in container terminals - Chua, Jason Zhen Sheng (2014)
With global trading business in the South East Asian region as well as the Greater Asian region growing rapidly, Singapore is well positioned to benefit from this upward trend of sea trade. Without expanding its resources to its maximum capacity in the various container terminals located throughout the country, Singapore will fall behind its competitors as the maximum workload increases yearly. In order to prevent such a scenario from happening, steps must be done to improve the container terminal efficiency to cope with workload for the foreseeable future. This project aims to help container terminal minimize the vessel turnaround time. By adapting the greedy heuristics onto a double yard crane single rail mounted gantry system, we hope to explore if this rule can be extended to this setup accounting for job tardiness with two yard cranes. From this project, it shows that the combination of the ATCRSS and greedy algorithm can be applied on a double yard crane single rail mounted gantry with an additional factor which includes the safety distance between the service crane as well as the physical limitations of the yard crane setup.